COVID-19 pandemic as a trigger for digitalization of the society, state and business - T. Yu. Krotenko (Управление)
The purpose of the article is to outline the changes that are taking place with the modern economic system. The article discusses some of the driving forces and circumstances of her deficient condition. The coronavirus pandemic is seen as a «collider», as an accelerator of the transition to a new model of the global economy. Its basic features are just being outlined, but a general conscious desire to streamline and automate many processes, to the reasonable digitalization of society, the state and business is already noticeable. The author points to the beginnings of transformation processes in the complex of productive forces and production relations, focuses special attention on those qualitative changes that were prompted by both the pandemic itself and the measures to combat it. These results appeared due to the use of the following methods: a) analysis of scientific reviews and articles devoted to the problems of diagnosing the need and readiness for automation of public, state and organizational processes; b) an expert survey conducted online during the «autumn quarantine» (2021), it was at this time that the problems of adapting to extreme changes, and the need for research and a practical look at the issues of intellectualization of transformational processes in society, state, and business, became significantly aggravated; c) content analysis of answers to open questions offered to respondents. The conclusions are drawn about the urgent need for the creation of useful technologies, their competent implementation in specific conditions and the formation of a benevolent regulatory environment. This is important not only from a theoretical point of view, but also for the practical preservation of the pace of digital transformation, sustainable economic development, and public good.